Spatio-temporal description of AIDS-related cancers incidence in north and sub-Saharan Africa and of mortality in HIV-infected patients in Algeria and hepatitis C prevalence in patients with non-Hodgkin lymphoma in Algeria - (:unkn) unknown (My University, 2013)
Background: In Africa, the prevalence of HIV/AIDS and hepatitis C virus (HCV) has been the highest in the world. Furthermore, cancer incidence is increasing. Objective: This thesis work presents a part of the impact of these infections on the cancer burden in northern and sub-Saharan Africa. AIDS-related cancers, namely Kaposi sarcoma (KS), non-Hodgkin lymphoma (NHL), and cervical cancer, were described to assess the impact of HIV/AIDS on cancer epidemiology in Algerian, Tunisian, Egyptian, Ugandan, and Zimbabwean populations. Furthermore, for the impact of HCV infection, the epidemiology of NHL as an extra-hepatic HCV-related cancer was also studied. Results: Ugandan HIV/AIDS prevalence has declined since the early 1990s, and in Zimbabwe, after an increase until the end of the 1990s, rates have gone down. In Algeria, the retrospective study performed during this thesis work showed that risk of death and standardized mortality ratio, comparing the mortality of HIV-positive patients with that of the general population, have decreased after the introduction of highly active antiretroviral therapy (HAART) in 1998 in Algeria. However, the late stage of the disease among HIV/AIDS patients at diagnosis warns of the high risk of HIV/AIDS transmission. These observations suggest that Algeria needs to couple HAART use with a more effective prevention programme to fight the increase in the number of HIV/AIDS cases. KS incidence was higher in the sub-Saharan African populations studied than in the northern African populations; however, among women it was similar in Uganda and Zimbabwe. With the emergence of the HIV/AIDS epidemic, KS incidence increased dramatically in both sub-Saharan African populations studied, and it has followed the HIV/AIDS time trend in Zimbabwe. However, in Uganda although HIV/AIDS prevalence has decreased, KS incidence has remained stable among women and elderly men (>50 years old). The decrease in KS incidence was observed only in
Keywords: African Research